Gene Expression Analysis of the Mechanism of Natural Sb(V) Resistance in Leishmania donovani Isolates from Nepal - Decuypere, Saskia (American Society for Microbiology, 2005)
Control of visceral leishmaniasis (VL) is being challenged by the emergence of natural resistance against the first line of treatment, pentavalent antimonials [Sb(V)]. An insight into the mechanism of natural Sb(V) resistance is required for the development of efficient strategies to monitor the emergence and spreading of Sb(V) resistance in countries where VL is endemic. In this work, we have focused on the mechanism of natural Sb(V) resistance emerging in Nepal, a site where anthroponotic VL is endemic. Based on the current knowledge of Sb(V) metabolism and of the in vitro trivalent antimonial [Sb(III)] models of resistance to Leishmania spp., we selected nine genes for a comparative transcriptomic study on natural Sb(V)-resistant and -sensitive Leishmania donovani isolates. Differential gene expression patterns were observed for the genes coding for 2-thiol biosynthetic enzymes, gamma-glutamylcysteine synthetase (GCS) and ornithine decarboxylase (ODC), and for the Sb(III) transport protein aquaglyceroporin 1 (AQP1). The results indicate that the mechanism for natural Sb(V) resistance partially differs from the mechanism reported for in vitro Sb(III) resistance. More specifically, we hypothesize that natural Sb(V) resistance results from (i) a changed thiol metabolism, possibly resulting in inhibition of Sb(V) activation in amastigotes, and (ii) decreased uptake of the active drug Sb(III) by amastigotes.